2017
DOI: 10.3390/nu9050463
|View full text |Cite
|
Sign up to set email alerts
|

Association between Picky Eating Behaviors and Nutritional Status in Early Childhood: Performance of a Picky Eating Behavior Questionnaire

Abstract: Picky eating behaviors are frequently observed in childhood, leading to concern that an unbalanced and inadequate diet will result in unfavorable growth outcomes. However, the association between picky eating behaviors and nutritional status has not been investigated in detail. This study was conducted to assess eating behaviors and growth of children aged 1–5 years from the Seoul Metropolitan area. Primary caregivers completed self-administered questionnaires and 3-day diet records. Differences in the nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
23

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 38 publications
1
31
0
23
Order By: Relevance
“…Picky eating is a frequent eating problem in childhood that concerns many parents. In young children, picky eating can contribute to a poor dietary intake and growth status and may have long-term effects (19) . Moreover, the eating behavior of early childhood, including food refusal, a common problem for pediatric practitioners, is a topic without clarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Picky eating is a frequent eating problem in childhood that concerns many parents. In young children, picky eating can contribute to a poor dietary intake and growth status and may have long-term effects (19) . Moreover, the eating behavior of early childhood, including food refusal, a common problem for pediatric practitioners, is a topic without clarity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the eating behavior of early childhood, including food refusal, a common problem for pediatric practitioners, is a topic without clarity. The prevalence rates vary from 13% to 22% or 13% to 50%, depending on the age (19)(20)(21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…Pengumpulan data melalui wawancara dengan bantuan kuesioner meliputi data karakteristik anak (usia dan jenis kelamin), perilaku picky eater, dan data asupan gizi dengan metode recall 2x24 jam. Kuesioner picky eater terdiri dari 13 pertanyaan yang disesuaikan dengan Goh dan Jacob (2012) serta Kwon et al (2017). Penentuan perilaku picky eater berdasarkan hasil skor dari skala likert.…”
Section: Pendahuluanunclassified
“…Of the 15 studies reviewed, 9 articles were found which mentioned a positive relationship between eating and growth and the 6 articles mentioned were not related. From 9 articles that positively related to the growth of children, 3 articles mentioned the correlation in increasing body weight and 6 articles mentioned the correlation between the occurrence of weight loss (Chao, 2018;Galloway, Watson, Pitama, Farrow, & Llewellyn, 2018;Kwon, Shim, Kang, & Paik, 2017;Viljakainen, Figueiredo, Rounge, & Weiderpass, 2019;Volger et al, 2017). 6 articles that are negatively related, mention that the growth of children remains stable or normal but only related to diet or nutritional intake is even just an excessive concern by parents.…”
Section: Correlate Picky Eating In Children Growthmentioning
confidence: 99%